Effect of radioiodine therapy (131I) on blood cells of differentiated thyroid carcinoma patients - Giang An, Nguyen Thi; Quang Trung, Nguyen (Vietnam Journal of Biotechnology, 2021)
Thyroid cancer accounts for about 1% of all types of cancers, with about 80% of cases being differentiated and 20% undifferentiated. Our study was conducted on 209 Differentiated Thyroid Carcinoma (DTC) patients treated at the Department of Nuclear Medicine of Nghe An Cancer Hospital with 91.39% of patients having papillary thyroid carcinoma, with the mean age of 47.91 ± 12.08. The geographic distribution of these patients was determined to be 68.42% coastal plains. Patients living in mountainous areas accounted for only 6.22%. For our experiment, treatment for patients including having the tumor removed and thyroid tissue destroyed using 131I. Patients were then prescribed with alternative hormones varying at different doses depending on the degree and stage of cancer. Among 209 patients, 8 patients were treated with 30mCi dose(3.83%); 196 patients treated with the dose of 100–150 mCi (93.78%) and 5 patients treated 200–250 mCi (2.39%). After 3–5 days of treatment, we observed significant changes in blood count with p<0.05. Initially, erythrocytes and hemoglobin count decreased slightly for 30–150 mCi dose patients but with 200–250 mCi dose patients, those indexes fell below the reference level. The platelet index decreased significantly after 3–5 days of treatment (p<0.05). Total leukocytes, lymphocytes and mono count decreased sharply after treatment (p<0.05) but neutrophils changed very little. After 3–6 months of treatment, the blood cell formula gradually stabilized, the recovery of red blood cells took place faster than the white blood cells and platelets. The recovery of blood cells of patients treated with doses of 200–500 mCi took place more slowly (p<0.05). Thus, the use of 131I in the treatment of DTC is a common and effective method, but they may also be at risk of impairing blood cells, especially in high-dose 131I patients. However, this change is still within the allowable limits and after 6 months of treatment, the blood cell counts tend to return to their original values. The speed of recovery depends on the individual blood cell line and the amount of treatment. This research result can be used as a reference for deciding on 131I dosage and supportive measures, interventions in treatment, helping patients avoiding the decrease of blood cells and increase the effectiveness of the treatment process.